SEJARAH HUKUM KONSTITUSI MADINAH NABI MUHAMMAD SAW - Zayyadi, Ahmad (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbstractThis work is of the historical discourse about the constitution Medina of law with the Medina Charter of The Prophet Muhammad as the content analysis and tends to find out moral massages, values, and principles therein to be implemented for the development of highly-plural Indonesian people. The history of the establishment of the Medina Law is closely related to the discourse about the charter of Medina which is still relevant to speak about. To sharpen the analysis of this work, I quote words from both western scholars and moslem ones and then understand them in the context of social life of the citizens of Indoenesia, especially in resolving social conflicts among peoples and ethnics. In additions, it may be suggested to be a resolution of religious conflicts at local, regional, and international levels. This work has, of course, relevance for the values in the Medina charter as a principle of the establishment of law-based nation are very important to be applicable in Indonesia. The human right, the unity of citizens, religion-based community, the protection for the minority, the politic of peace, etc. are fundamental basic of the values of civilization once practiced by the Prophet Muhammad through the charter of Medina as the fondation of the state law.Key words: history, state law, the Medina constitution, ummah, the charter of Medina.